The Role of Tax Policies, Inflation, Trade Openness and Exchange Rate Volatility on the Foreign Investment Decisions in Pakistan - Aqsa Shabbir; Shahid Abbas; Imran Javed; Numair Nisar (Indus Journal of Social Sciences, 2025)
Foreign investment decisions have been the challenging issue nowadays due uncertainty of financial condition around the globe. This aspect need the focus of recent studies and the present study examines the impact of tax policies, inflation, trade openness and exchange rate volatility on the foreign investment decisions in Pakistan. The study used the secondary data extracted from the World Development Indicators (WDI) from 1991 to 2024. The outcomes revealed that the tax policies, inflation and trade openness have a positive association with foreign investment decisions and exchange rate volatility has a negative association with foreign investment decisions in Pakistan. The study provides the help to the policymakers in establishing new policies related to enhance the foreign investment decisions using effective tax policies and low exchange rate volatility.